European experience and Ukrainian realities in the policy of financial support entrepreneurial sector - Savchenko, Olga; Poberezhnyi, Roman (University of Economics in Katowice, 2017)
Aim/purpose – We want to provide recommendations to bridge the gap in access to financing of the entrepreneurial sector in Ukraine based on the analysis of European experience, EBF approaches, financial funds for SMEs and the current state of the credit market in Ukraine. Design/methodology/approach – We used the general scientific methods of knowledge, conceptual tenets of the theory of market economy, abstract logical analysis and synthesis, induction and deduction, historical (to determine the nature and causes of bank investment in SMEs, refine categories and terms); formalization, systems analysis (to determine factors of investment banking, institutional and legal environment); statistical, retrospective analysis. The results of surveys conducted by the EBF on the issues of support and development of SMEs are used, own research of 120 Ukrainian SMEs, which was conducted during the period from January to July 2016. The nature of the research questions was reinforced by the decision to survey only SMEs. Independent reporting (from entrepreneurs or CEOs) was used to account for both business activity and the external sources of information. Findings – Policy initiatives should primarily be developed at the national level in the field of lending to SMEs based on the European experience and Ukrainian realities; it is necessary to develop an understanding of the need for access to certain types of information; SMEs are the main providers and the most valuable source of credit information. Research implications/limitations – When using the methods of calculation creditworthiness perhaps to take into account the methods for assessing the quality of management, the image of the enterprise, ISO certificates. Originality/value/contribution – Based on the cross-country comparison of the EU and Ukraine, highlight the necessity of focusing on some legal unification of SME lending procedures for the development of a culture of sustainable entrepreneurship on the European continent.
Keywords: credit; SMEs; loan; bank; investors